(untitled) (Pedagogy of Higher and Secondary Education, 2009)
Different approaches dealing with formulating pupils’ of the last forms vocal-chorus abilities in the classes of chorus in the condition of musical school are considered in this article. The main notions are defined and the peculiarities of accomplishment of vocal-chorus exercises are based.